Effect of hexagonal boron nitride on the coefficient of frictions of organic-inorganic hybrid polymer thin films for metal surface coatings - Karadag, Mehmet; Karaahmet, Oguz; Cicek, Bugra; Usta, Mustafa Ilker (TAYLOR & FRANCIS LTD, 2020)
Organic-inorganic hybrid coatings were developedviaa sol-gel method using hexagonal boron nitride (h-BN) as a ceramic filler material incorporated into a polymeric matrix. To investigate the effects of h-BN on the properties of polymer-based coatings, parameters such as hardness, coefficient of friction, and hydrophobicity were investigated. Colloidal silica (CS), methyltrimethoxysilane (MTMS), water, and acid catalyst containing coatings were prepared by varying the content of h-BN from 10% to 25%. All the coatings were prepared with the same experimental procedure and coated on 1050 aluminum alloy plates. The compensating contents of MTMS and colloidal silica with a fixed molar ratio of MTMS and CS were set to be 1:1.2, and a specific amount of the catalyst was utilized. Coatings were examined by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), and energy-dispersive X-ray spectroscopy (EDS). The most promising physical properties were determined to be the pencil hardness of 8B, adhesion strength of 5B, coefficient of friction of 0.332 N, and water contact angle of 114.75 degrees. Therefore, it can be concluded that the h-BN improves the physical properties of polymeric coatings. In addition, this study demonstrates the effect of h-BN on the adherence of polymer matrix-based hybrid coatings.
Keywords: Hexagonal boron nitride; sol-gel; colloidal silica; methyltrimethoxysilane; friction; SOL-GEL COATINGS; H-BN; TRIBOLOGICAL BEHAVIOR; MECHANICAL-PROPERTIES; CORROSION PROTECTION; COMPOSITES; TEMPERATURE; NANOPARTICLES; LUBRICATION; PERFORMANCE; Engineering; Materials Science; Mechanics